2021
DOI: 10.1002/adsc.202100938
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Four‐Component Cascade Reaction for the Construction of Triazoles Bearing β‐Hydroxy Chalcogenides

Abstract: A copper-catalyzed four-component cascade reaction for the preparation of triazoles bearing β-hydroxy chalcogenides from terminal alkynes, azides, epoxides, and Se/K 2 S is reported. The present reaction proceeds under mild conditions, and exhibits a good functional group compatibility. A possible mechanism is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Based on the proposed reaction mechanism (Figure S26), we present four options on how to avoid this undesired reactivity. 14,27,30,38 We validated the approaches using the propargyl tyrosine probe 2 (0.3 mM, 24 h) in living SH-SY5Y cells, which provides strong metabolic labeling of alpha-tubulins catalyzed by tubulintyrosine ligase (TTL) corresponding to a molecular weight around 55 kDa. 19,39,40 The metabolic labeling was compared with the probe added directly to the cell lysate before the initiation of CuAAC (Figure 6A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the proposed reaction mechanism (Figure S26), we present four options on how to avoid this undesired reactivity. 14,27,30,38 We validated the approaches using the propargyl tyrosine probe 2 (0.3 mM, 24 h) in living SH-SY5Y cells, which provides strong metabolic labeling of alpha-tubulins catalyzed by tubulintyrosine ligase (TTL) corresponding to a molecular weight around 55 kDa. 19,39,40 The metabolic labeling was compared with the probe added directly to the cell lysate before the initiation of CuAAC (Figure 6A).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“… The combined analyses of the diagnostic ions and fragments acquired using high-resolution MS strongly corroborate the presence of the thiotriazole ring, connecting together the three components of the reaction. This is in line with the previously reported interrupted Cu-catalyzed azide–alkyne cycloaddition forming 5-thiotriazole in a multicomponent reaction containing a terminal alkyne, azide-containing scaffold, and elemental sulfur or sulfide salts. , Of note, the latter paper using sulfides takes advantage of air oxygen as an oxidation agent. To show the relevance of thiotriazole product formation after metabolic labeling, SH-SY5Y cells were incubated with 0.2 mM of probe 4 for 8 h. Similarly as above, the resulting modified peptides after CuAAC with the DTB-tag were specifically enriched to show over 900 thiotriazole conjugated peptides (∼60% of all peptide IDs) and equal diagnostic ions supporting the thiotriazole structure (Figures I and H, S7, and Tables S4 and S5).…”
Section: Resultsmentioning
confidence: 99%
“…Although significant advances have been made to access selenotriazoles, synthesis of diseleno-triazoles from terminal alkynes via such a strategy remained underexplored. With our growing interest in azide–alkyne cycloaddition, herein, we reported a copper-catalyzed cascade multicomponent reaction of azides, terminal alkynes, and selenium to synthesize ditriazolyl diselenides (Scheme b).…”
Section: Intruductionmentioning
confidence: 99%
“…Li et al reported a copper-catalyzed four-component cascade reaction. Based on this strategy, triazoles bearing β-hydroxy chalcogenides 25 can be prepared from terminal alkynes, azides, epoxides and Se/K 2 S. The present reaction utilized sustainable selenium and sulfur reagents under mild conditions and exhibited good functional group compatibility for both electron-donating and electron-withdrawing groups 39 (Scheme 13).…”
Section: Multicomponent Reactions Of Azides To Construct 123-triazolesmentioning
confidence: 99%